2018
DOI: 10.29252/j.health.9.2.182
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Behavioral Processes and Its Stages of Change for Fruit and Vegetable Consumption among Nursing and Midwifery Staff of Ardabil Hospitals, 1395: Application of the Trans Theoretical Model

Abstract: Background & objectives: Inappropriate nutrition places employees at risk of being overweight or obese, and not only affect their health but also indirectly may affect patients. The trans-theoretical model is one of the most common models of health promotion. It is recognized as one of the ways of identifying and changing diet, especially increasing the consumption of fruits and vegetables. In this model, behavioral changes can be seen in stages. Therefore, this study designed to determine the status of cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…Behavioral processes of change (such as self-liberation and stimulus control) were other motivators and predictors of helmet use, therefore training and disseminating rules and stimulators which can remind helmet use to motorcyclists is recommended. This finding is in line with other health-related studies (17,18). Similar with the results of other health-related studies (17)(18)(19)(20), counter conditioning as a behavioral process of change (e.g.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Behavioral processes of change (such as self-liberation and stimulus control) were other motivators and predictors of helmet use, therefore training and disseminating rules and stimulators which can remind helmet use to motorcyclists is recommended. This finding is in line with other health-related studies (17,18). Similar with the results of other health-related studies (17)(18)(19)(20), counter conditioning as a behavioral process of change (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in line with other health-related studies (17,18). Similar with the results of other health-related studies (17)(18)(19)(20), counter conditioning as a behavioral process of change (e.g. instead of wearing a hat or nothing on my head when I ride a motorcycle) was a motivator to start helmet use, therefore the theory-based education can focus on this sub-construct to motivate motorcyclists to use helmets.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Other models and theories have also been applied to develop instruments regarding the predictors of F&V intake such as the theory of planned behaviour and the stages of change model. For instance, Babazadeh et al ( 59 ) and Narimani et al ( 60 ) developed their instruments based on the theory of planned behaviour and the stages of change model with reliability coefficients of 0·82 and 0·87, respectively. Therefore, considering the reliability coefficient in the present study (0·84), it can be stated that the reliability scores of instruments in these studies developed through three different theories or models were approximately equal.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] In another study conducted by Vakili et al on the general population of Mashhad in 2014, the results revealed that only about half of the participating men and women regularly consumed fruit, and the situation was even worse for consuming vegetables. [ 12 ] Narimani et al also reported that the majority of nursing and midwifery staff in Ardabil teaching and medical centers (77.3%) were in the inactive stages of changing the behavior of consuming F and V.[ 13 ] As quoted from Tassitano et al in their article, although there is evidence of environmental, economic, social, and demographic determinants in the documented scientific literature, understanding psychosocial factors can be the key to developing effective behavioral interventions to increase F and V consumption. [ 14 ] In this regard, it is very important to develop programs with an emphasis on the need to consider the facilitators of consuming F and V. The findings of Kasten et al in the Netherlands showed that high levels of intention and self-efficacy as well as strong habits of consuming F and V clearly help to develop action plans.…”
Section: Introductionmentioning
confidence: 99%